The afterlife of site-specific sculpture: a self-referential study through practice - Kim, M (2021)
As practice-led research, this thesis takes the form of a portfolio documenting a series of works and exhibitions through which that research was conducted. It explores issues related to site-specific sculpture and begins by examining my existing methods of site-specific sculptural intervention within the exhibition environment. This raises some problematic issues regarding the temporality of site-specific sculpture, which are brought into clearer focus in my subsequent experiments in exhibition making. In the next transitional phase, the inflexibility of my previous approach is dissolved to a degree, which opens up possibilities for new sculptural and installation practices in several alternative directions.